Intracellular glycolysis in brown adipose tissue is essential for optogenetically induced nonshivering thermogenesis in mice - Jeong, Jae Hoon (Sci Rep, 2018)
Release of fatty acids from lipid droplets upon activation of the sympathetic nervous system (SNS) is a key step in nonshivering thermogenesis in brown adipose tissue (BAT). However, intracellular lipolysis appears not to be critical for cold-induced thermogenesis. As activation of the SNS increases glucose uptake, we studied whether intracellular glycolysis plays a role in BAT thermogenesis. To stimulate BAT-innervating sympathetic nerves in vivo, we expressed channelrhodopsin-2 (ChR2) in catecholaminergic fibers by crossbreeding tyrosine hydroxylase-Cre mice with floxed-stop ChR2 mice. Acute optogenetic stimulation of sympathetic efferent fibers of BAT increased body temperature and lowered blood glucose levels that were completely abolished by the β-adrenergic receptor antagonist. Knockdown of the Ucp1 gene in BAT blocked the effects of optogenetic stimulation on body temperature and glucose uptake. Inhibition of glucose uptake in BAT and glycolysis abolished optogenetically induced thermogenesis. Stimulation of sympathetic nerves upregulated expression of the lactate dehydrogenase-A and -B genes in BAT. Optogenetic stimulation failed to induce thermogenesis following treatment with the LDH inhibitor. Pharmacological blockade and genetic deletion of the monocarboxylate transporter 1 completely abolished the effects of sympathetic activation. Our results suggest that intracellular glycolysis and lactate shuttle play an important role in regulating acute thermogenesis in BAT.